Compact metamaterial inspired periwinkle shaped fractal antenna for multiband applications - T P Madhav, B; Venkateswara Rao, M; Manisahithi, K; S S Sarvani, D; Dharani, M; V Rami Reddy, S (International Journal of Engineering and Technology, 2017)
A compact periwinkle flower shaped fractal antenna loaded with split-ring resonator on either side of the feedline is proposed in this article. The proposed antenna consists of partial ground on flipside and a periwinkle flower petal is located on the rectangular patch. The proposed antenna works in multiband i.e., at 4.1GHz,4.5GHz,4.8Ghz(S-band) at 6.7GHz,6.75GHz(C-band) at 9.4GHz(X-band) and at 12.7(ku) i.e., proposed antenna covers almost one frequency at all radar frequency bands. The proposed antenna has been analyzed and maximum gain of 4dB and radiation efficiency of 87 percent is observed.